Directed Evolution of P450 Fatty Acid Decarboxylases via High‐Throughput Screening towards Improved Catalytic Activity. Issue 1 (28th October 2019) - Xu, Huifang; Liang, Weinan; Ning, Linlin; Jiang, Yuanyuan; Yang, Wenxia; Wang, Cong; Qi, Feifei; Ma, Li; Du, Lei; Fourage, Laurent; Zhou, Yongjin J.; Li, Shengying
Abstract: P450 fatty acid decarboxylases (FADCs) have recently been attracting considerable attention owing to their one‐step direct production of industrially important 1‐alkenes from biologically abundant feedstock free fatty acids under mild conditions. However, attempts to improve the catalytic activity of FADCs have met with little success. Protein engineering has been limited to selected residues and small mutant libraries due to lack of an effective high‐throughput screening (HTS) method. Here, we devise a catalase‐deficient Escherichia coli host strain and report an HTS approach based on colorimetric detection of H2 O2 ‐consumption activity of FADCs. Directed evolution enabled by this method has led to effective identification for the first time of improved FADC variants for medium‐chain 1‐alkene production from both DNA shuffling and random mutagenesis libraries. Advantageously, this screening method can be extended to other enzymes that stoichiometrically utilize H2 O2 as co‐substrate. Abstract : Enzyme Catalysis : A novel high‐throughput screening method that utilizes a catalase‐deficient Escherichia coli host combined with efficient enzyme release and colorimetric detection of H2 O2 ‐depletion enabled quick identification of P450 peroxygenase variants with improved free fatty acid conversion activity to produce 1‐alkenes. This method can be generally applicable to vast biocatalysts with H2 O2 as co‐substrate.